How overloaded employees can use resilience and forgiveness resources to overcome dissatisfaction and maintain their knowledge-sharing efforts - De Clercq, D.; Pereira, R. (International Journal of Organizational Analysis, 2025)
Purpose Drawing on conservation of resources theory, this study aims to examine how employees’ experiences of excessive workloads may direct them away from efforts to share knowledge with other organizational members, as well as the circumstances in which this process is more or less likely. To untangle the process, the authors predict a mediating role of job dissatisfaction and moderating roles of two complementary resources that help employees cope with failure: resilience as a personal resource and organizational forgiveness as an organizational resource. Design/methodology/approach Survey data were gathered from employees of an organization that operates in the construction retail sector. The Process macro provides an empirical test of the moderated mediation dynamic that underpins the proposed conceptual framework. Findings The statistical findings affirm that an important channel through which employees’ perceptions that their work demands are unreasonable escalate into a diminished propensity to share knowledge is their lack of enthusiasm about their jobs. Their ability to recover from challenging work situations and their beliefs that the organization does not hold grudges against people who commit mistakes both mitigate this harmful effect. Practical implications For organizational practitioners, this research shows that when employees feel frustrated about extreme work pressures, the resource-draining situation may escalate into diminished knowledge sharing, which might inadvertently undermine their ability to receive valuable feedback for dealing with the challenges. From a positive perspective, individual resilience and organizational forgiveness represent resources that can protect employees against this negative spiral. Originality/value This study explicates an unexplored harmful effect of strenuous workloads on knowledge sharing, which is explained by employees’ beliefs that their organization fails to provide satisfactory job experiences. This effect also is mitigated to the extent that employees can draw from valuable personal and organizational resources.